Judicialização da saúde, ativismo judicial e o consequente desequilíbrio do orçamento público - Silva, Juvêncio Borges [UNESP]; Jucatelli, João Paulo (Centro de Ensino Unificado de Brasilia, 2017)
Judicialization and judicial activism is a reality that permeates the economic, political, social, scientific Brazilian society in recent times. There are several causes that gave rise according to different authors who have dedicated themselves to the subject, however, having in common the view that the Constitutional documents, especially those re-adapetd and/or promulgated in the 2nd post World War period, are the fertile field cultivation, concentrating and materializing all these elements. These are essential phenomena to the administration of justice and the preservation of the constitutional democratic order before the representational deficit elective powers to the company in the current national political context, however, on behalf of this process it is manifested Power of interference signals judiciary in the face of the other branches of government, whose discussion on the agenda objects the legitimacy of interference, to the extent that they impose obligations whose financial costs cause actual breakdowns in public budgets, putting at risk the organization and implementation of public policies prioritized by each these spheres of power of the Republic, complaining, so that limits are set to this practice in order to ensure balance and independence of all powers .
Legalization of health, judicial activism and the resulting imbalance of the public budget
Keywords: Judicial activism; Legalization; Public budget; Public health